Pendidikan Humanis dan Dialogis: Implementasi Pemikiran Paulo Freire dalam Bimbingan dan Konseling - Susanti, Meri; Marsidin, Sufyarma; Karneli, Yeni (Jurnal Kajian dan Pengembangan Umat, 2024)
The implementation of education is currently still indicated to be in oppression. This condition can be seen from the process that positions students as educational objects. Meanwhile, students are the subject of education. Education should be carried out with a fun, active and creative process. To overcome the shackles and realize liberating education, it is carried out by implementing the educational process proposed by Paulo Freire. Teachers are the spearhead in organizing education in a humanist and dialogical manner. Education takes place by implementing dialogue interactively, with love, humility, trust, critical thinking and hope for students. This research Journal of Ummah Studies and Development p aims to uncover humanist and dialogical education based on Paulo Freire's thought and its implementation in guidance and counseling services. This research was conducted using literature research. Data was collected by examining sources derived from articles and books. The results of the study prove the importance of humanist and dialogical education in removing the shackles of oppression in education, by placing students as active subjects in learning. To create active and creative students as subjects in education, it is necessary to have an educational process that is carried out by mutual respect for the dignity and dignity of students, social justice, reality-based, freedom in undergoing the process, cooperative, having the opportunity to express creative thoughts with love, humility, trust, and hope. Humanist and dialogical education is a discourse offered to overcome the ice and shackles in education. The implementation of guidance and counseling services in the educational environment, assists students in overcoming various problems, and achieves their development optimally.